Mauritius on fire: Tracking historical human impacts on biodiversity loss. (8th October 2017) - Gosling, William D.; de Kruif, Jona; Norder, Sietze J.; de Boer, Erik J.; Hooghiemstra, Henry; Rijsdijk, Kenneth F.; McMichael, Crystal N. H.
Abstract: Fire was rare on Mauritius prior to human arrival (AD 1598); subsequently three phases of elevated fire activity occurred: ca 1630–1747, 1787–1833, and 1950–modern. Elevated fire frequency coincided with periods of high human impact evidenced from the historical record, and is linked to the extinction of island endemics.